SISTEM KEAMANAN BARANG DI LOKER DENGAN DETEKSI WAJAH MENGGUNAKAN METODE TRIANGLE FACE - M Irfan Fahmi; Hidayatullah Hidayatullah (RJOCS (Riau Journal of Computer Science), 2018)
Triangle Face method is one of the face structure and using the digital image. This Method must be processed corectily for detecting the facial features and it’s structure should be identified carefully and showed the comparison . Resulting face must be converted to each other . Method of recognition for human face, hand and feet are considered to make efrectiveway to learn it and safe. Because this method is aimed to produce the deposit counter system in the locker for detecting without ID Card